PENGEMBANGAN MODUL BERBASIS GUIDED INQUIRY LABORATORY UNTUK MENINGKATKAN LITERASI SAINS DIMENSI PROSES MATERI SISTEM PENCERNAAN PADA KELAS XI - Prima Maya Natalia; Maridi Maridi; Suciati Suciati (INKUIRI: Jurnal Pendidikan IPA, 2016)
The purpose of this research is to find out: 1) the characteristics module based on guided inquiry laboratory to improve process dimension of students’ scientific literacy on the Digestive System material of XI grade; 2) the feasibility module based on the guided inquiry laboratory to improve process dimension of students’ scientific literacy on the Digestive System material of XI grade; 3) the effectiveness module based on guided inquiry laboratory to improve process dimension of students’ scientific literacy on the Digestive System material of XI grade. This Research and Development (R & D) is modified from Borg and Gall (1983). The development of module based on guided inquiry laboratory was done through 10 stages: 1) research and information collecting; 2) planning; 3) develop preliminary form of product; 4) preliminary field testing; 5) main product revision; 6) main field testing; 7) operational product revision; 8) operational field testing; 9) final product revision; and 10) dissemination and implementation. The validation of product development was done by a material expert, presentation of module expert, language expert, learning instrument expert. The main fields of research subjects with 67 students which consist of two classis use module, 34 students of XI grade of science class first and 33 students of XI grade of science class fourth with 67 students. The result of process dimension of students’ scientific literacy was analyzed by using normalized N-gain to investigate the effectiveness of module based on guided inquiry laboratory. Paired T-test to investigate process dimension of students’ scientific literacy before and after using module based on guided inquiry laboratory.  The results of this research and development is: 1) the characteristics of module based on guided inquiry laboratory is developed based on syntax guided inquiry laboratory which is: observation, manipulation, generalization, verification, and applications; 2) The result of validation module based on guided inquiry laboratory by expert has “very good” category (92,89%); and 3) module based on guided inquiry laboratory is able to improve dimension process of student’s scientific literacy on the Digestive System material of XI grade. The results of analysis non-parametric Wilcoxon test showed  that XI grade of science class first and XI grade of science class fourth had index of probability (p) <0.05, so H0 was rejected, there’s difference of the result before and after using modul based on guided inquiry laboratory. Based on this data it can be concluded that using module based on guided inquiry laboratory effective and feasible to improve process dimension of students’ scientific literacy in Digestive System material of XI grade.